Analisis Hukum Terhadap Pelaksanaan Perjanjian Pemborongan Jalan Masuk Rusunawa Antara Dinas Pekerjaan Umum Kota Balikpapan Dengan CV. Putra Nurul Sejati - Fakultas Hukum Universitas Mulawarman (Fakultas Hukum Universitas MUlawarman, 2012)
Mutilation of road effect of effort coal mining so bother consumer of road which initialy function as or public of provinsi become private interest or importance of body is effort resulting impact to mining surounding citizen environment in District Of Samarinda North. Target of this research is to know study punish and legal effort able to be in overcoming mutilation of road effect of effort coal mining in District of Samarinda North. Research type used empirical yuridis by using approach of law and regulation and approach of case which its research location in Road of HM Ardan and Road Padat Karya, District Of Sempaja North, District Of Samarinda North. And also analyse data descriptively qualitative to make deskripsi with studying environmental impact to mutilation of road effect of effort coal mining. Coal mining in the district of Samarinda North who use public transportation in the transportation can make use of public infrastructure and facilities after fulfilling the provisions of the legislation with the transport minister’s decision is based on attachment number 1 of 2003 KM of setting class path on the island of borneo and the company is one of the coal mining business there are specific rules in order not to damage public facilities such as the destruction of roads and damage the environment and government Samarinda city efforts in the destruction of road does not sanction either administrative sanction, civil sanction and criminal sanctions to the coal mining business as well as vehicles used to transport the coal charge, no class exceeds the predetermind path In this case better be strived again by Government of City Samarinda by observation and make By Law concerning obligation company of coal mining to build special road of coal mine. Then strive management and responsibility also in usage common road as special road of coal mine.